Pamphlets and politics in the Dutch Republic - Deen, Femke; Onnekink, David; Reinders, Michel, 1979- (Leiden ; Boston : Brill, 2011)
The Handpress World explores the impact of the invention of printing by moveable type from the first experiments of the incunabula age through to the end of the eighteenth century. In this crucial period of book history the new technology both transformed established markets for scholarly and religious literature and found a new public through the rise of the pamphlet and later the newspaper. The series will investigate every aspect of this cultural transformation, from the promotion in print of the great intellectual movements of the day through to the birth of the public library. Femke Deen)
Introduction. Pamphlets and politics : introduction / Femke Deen, David Onnekink and Michel Reinders ; Return to the land of blue little books / Craig Harline -- The pamphlet and its function. Thievery of literature : consequences of the interaction between politics and commerce for the form and content of pamphlets / Roeland Harms ; Political pamphleteering and public opinion in the age of De Witt (1653-1672) / Guido de Bruin ; The citizens come from all cities with petitions : printed petitions and civic propaganda in the seventeenth century / Michel Reinders -- The pamphlet as an historical actor. Poison in print : pamphleteering and the deaths of Concini (1617) and the brothers De Witt (1672) / Jill Stern ; The revolution in Dutch foreign policy (1688) / David Onnekink ; Economic reform and neutrality in Dutch political pamphlets (1741-1779) / Koen Stapelbroek -- Public debate and the media. Handwritten propaganda : letters and pamphlets in Amsterdam during the Dutch Revolt (1572-1578) / Femke Deen ; Peace or no peace : the role of pamphleteering in public debate in the run-up to the twelve-year truce / Monica Stensland.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Netherlands -- Politics and government -- 1556-1648.; Netherlands -- Politics and government -- 1648-1714.; Netherlands -- Politics and government -- 1714-1795.; Pamphlets -- Netherlands -- History; Pamphleteers -- Netherlands -- History; Political culture -- Netherlands -- History; Netherlands -- Intellectual life; Pays-Bas -- Politique et gouvernement -- 1556-1648.; Pays-Bas -- Politique et gouvernement -- 1648-1714.; Pays-Bas -- Politique et gouvernement -- 1714-1795.; Pamphlétaires -- Pays-Bas -- Histoire; Pays-Bas -- Vie intellectuelle; HISTORY -- General; Intellectual life; Pamphleteers; Pamphlets; Political culture; Politics and government; Netherlands; Politische Kommunikation; Pamphlet; Niederlande; Politische Kommunikation -- Niederlande -- Geschichte Neuzeit; Pamphlet -- Niederlande -- Geschichte Neuzeit; 1556-1795; History